Juvenile titanosaurian (Dinosauria: Sauropoda) remains from the Upper Cretaceous of Barreales Lake, Neuquén, Argentina. (March 2022) - Calvo, Jorge O.; Ramírez, Agustín; Salgado, Leonardo; Otero, Alejandro
Abstract: Remains of juvenile sauropods from the Upper Cretaceous Portezuelo Formation (Neuquén Group), at Barreales Lake (Neuquén Province), are identified and described. The material include a femur (14.6 cm length) and an anterior caudal vertebra (3.1 cm length). Their general morphology allows us to assign these bones to the Titanosauria. Although a specific assignation is impossible, in view of the fragmentary condition of the material, these bones are important because they expand our knowledge on the immature stages of titanosaurs. Highlights: Juvenile materials of titanosaurid sauropods. Upper Cretaceous materials of sauropods from Barreales lake, Neuquén Basin, Argentina. Neuquén Group, Portezuelo Formation, juevile materials from titanosaurid. A femur and a caudal from a titanosaurid sauropod of Neuquén province, Argentina.